1998
DOI: 10.1172/jci1899
|View full text |Cite
|
Sign up to set email alerts
|

Murine double nullizygotes of the angiotensin type 1A and 1B receptor genes duplicate severe abnormal phenotypes of angiotensinogen nullizygotes.

Abstract: Rodents are the unique species carrying duplicated angiotensin (Ang) type 1 (AT1) receptor genes, Agtr1a and Agtr1b. After separately generating Agtr1a and Agtr1b null mutant mice by gene targeting, we produced double mutant mice homozygous for both Agtr1a and Agtr1b null mutation (Agtr1a-/-; Agtr1b-/-) by mating the single gene mutants. Agtr1a-/-, Agtr1b-/- mice are characterized by normal in utero survival but decreased ex utero survival rate. After birth they are characterized by low body weight gain, marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
225
2
4

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(245 citation statements)
references
References 29 publications
13
225
2
4
Order By: Relevance
“…3C) exhibited severe hypotension. Although mice deficient for the gene encoding ATla (Agtrla-/-) showed milder hypotension than did those deficient for the gene encoding Agt-/-or Ace-/- (34,35), double nullizygotes without the genes for AT1a and AT1b (Agtrl-/-) were severely hypotensive (36,37) (Fig. 3D).…”
Section: Pregnancy-induced Hypertensionmentioning
confidence: 99%
“…3C) exhibited severe hypotension. Although mice deficient for the gene encoding ATla (Agtrla-/-) showed milder hypotension than did those deficient for the gene encoding Agt-/-or Ace-/- (34,35), double nullizygotes without the genes for AT1a and AT1b (Agtrl-/-) were severely hypotensive (36,37) (Fig. 3D).…”
Section: Pregnancy-induced Hypertensionmentioning
confidence: 99%
“…Targeted null mutations of genes of the major components of the RAS such as angiotensinogen (Agt) (Kim et al 1995), renin (Yanai et al 2000;Chen et al 2007), angiotensin-converting enzyme (ACE) Esther Jr. et al 1996), and AT 1 receptors (Ito et al 1995;Sugaya et al 1995;Matsusaka et al 1996;Oliverio et al 1998a,b;Tsuchida et al 1998) result in reduced blood pressure and abnormal renal vascular and tubular structures. AT 1A 2/2 mice have reduced blood pressure, slight papillary hypoplasia, hyperplasia of renin-producing granular cells (Ito et al 1995;Oliverio et al 1998b;Tsuchida et al 1998), and significantly dilated efferent arterioles (Harrison-Bernard et al 2003,2006.…”
mentioning
confidence: 99%
“…AT 1A 2/2 mice have reduced blood pressure, slight papillary hypoplasia, hyperplasia of renin-producing granular cells (Ito et al 1995;Oliverio et al 1998b;Tsuchida et al 1998), and significantly dilated efferent arterioles (Harrison-Bernard et al 2003,2006. AT 1B 2/2 mice show no significant differences in blood pressure, renal architecture (Chen et al 1997;Oliverio et al 1998a), or renal microvascular responses to ANG II (Harrison-Bernard et al 2006) compared with wild-type (WT) mice.…”
mentioning
confidence: 99%
“…This notion is supported by data obtained in mice with a double AT 1a (À/À) and AT 1b (À/À), which have a more severe phenotype with a significant lower body weight, kidney weight, blood pressure and heart rate than mice lacking only the AT 1a receptor. 46,52 AT 1 receptors are expressed in many organ systems, including the circulatory system, the central nervous system and the urinary system, and so on, 53 which are presumed to play key functions in blood pressure homeostasis. Interestingly, a cross-transplantation study between genetically matched AT 1 (À/À) and wild-type mice revealed that, for the development of Ang II-induced hypertension and cardiac hypertrophy, renal AT 1 receptors are required.…”
Section: Angiotensin II At 1 and At 2 Receptorsmentioning
confidence: 99%